Inhibition of KU70 and KU80 by CRISPR interference, not NgAgo interference, increases the efficiency of homologous recombination in pig fetal fibroblasts - Guo-ling LI; Rong QUAN; Hao-qiang WANG; Xiao-fang RUAN; Jian-xin MO; Cui-li ZHONG; Hua-qiang YANG; Zi-cong LI; Ting GU; De-wu LIU; Zhen-fang WU; Geng-yuan CAI; et al. (Journal of Integrative Agriculture, 2019)
Non-homologous end-joining (NHEJ) is a predominant pathway for the repair of DNA double-strand breaks (DSB). It inhibits the efficiency of homologous recombination (HR) by competing for DSB targets. To improve the efficiency of HR, multiple CRISPR interference (CRISPRi) and Natronobacterium gregoryi Argonaute (NgAgo) interference (NgAgoi) systems have been designed for the knockdown of NHEJ key molecules, KU70, KU80, polynucleotide kinase/phosphatase (PNKP), DNA ligase IV (LIG4), and NHEJ1. Suppression of KU70 and KU80 by CRISPRi dramatically promoted (P<0.05) the efficiency of HR to 1.85- and 1.58-fold, respectively, whereas knockdown of PNKP, LIG4, and NHEJ1 repair factors did not significantly increase (P>0.05) HR efficiency. Interestingly, although the NgAgoi system significantly suppressed (P<0.05) KU70, KU80, PNKP, LIG4, and NHEJ1 expression, it did not improve (P>0.05) HR efficiency in primary fetal fibroblasts. Our result showed that both NgAgo and catalytically inactive Cas9 (dCas9) could interfere with the expression of target genes, but the downstream factors appear to be more active following CRISPR-mediated interference than that of NgAgo.